The equilibrium risk premium on the forward market for foreign currency - Udo Broll; Bernhard Eckwert (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
This paper constructs an intertemporal model of the spot and forward markets for foreign exchange and shows that in equilibrium the forward market is unbiased, i.e., the forward rate is equal to the expected spot rate which will prevail in the market next period. This holds true as long as the monetary authorities do not exogenously intervene in the foreign exchange market. Our analysis suggests that nominal exchange rate variability can affect the real sector of the economy only if active intervention policies are carried out on the spot exchange market.
Keywords: F31; F33; 330; exchange rate risk; currency forward markets; risk premium; Währungsderivat; Risikoprämie; Theorie